Obsceniczne, obraźliwe czy „śmieszne”? O odbiorze społecznym kilku typów nazw miejscowych pogranicza polsko-wschodniosłowiańskiego - Koper , Mariusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
This article examines local place names which may, due to their form or their use in a wider context of a speech act, be considered to be obscene, offensive or funny. The first group includes names that evoke troublesome associations, even though they are not, etymologically speaking, connected with the taboo sphere (e.g. Gacie, Hujsko, Podupce). The second group consists of place names whose obscene or humorous character is recognisable only by those with relevant linguistic knowledge and awareness (e.g. Przedrzymiechy, Pukarzów, Tarzymiechy). The third and final group contains names whose potentially ridiculous and humorous character is present only when accompanied by a broader text and context of an utterance (e.g. Nielisz, Niemce, Cyców).